Studies in tectonic culture : the poetics of construction in nineteenth and twentieth century architecture - Frampton, Kenneth; Cava, John.; Graham Foundation for Advanced Studies in the Fine Arts. (Cambridge, Mass. : MIT Press, 1995)
This text aims to clarify the various turns that structural engineering and tectonic imagination have taken, showing how both constructional form and material character were integral to an evolving architectural expression.
"Graham Foundation for Advanced Studies in the Fine Arts, Chicago, Illinois."
Includes bibliographical references (pages [413]-420) and index.
ARC
Keywords: Symbolism in architecture; Architecture, Modern -- 19th century; Architecture, Modern -- 20th century; Architecture